Behandlung retroperitonealer Sarkome in Deutschland: eine Umfrage der Deutschen Gesellschaft für Allgemein- und Viszeralchirurgie, der Deutschen Interdisziplinären Studiengruppe Sarkome und der Patientenorganisation Das Lebenshaus = Treatment of retroperitoneal sarcoma in Germany : results of a survey of the German Society of General and Visceral Surgery, the German Interdisciplinary Sarcoma Study Group and the advocacy group Das Lebenshaus - Jakob, Jens; Gerres, Anna; Pilz, Lothar R.; Kasper, Bernd; Hohenberger, Peter (Der Chirurg, 2018)
Objective: Retroperitoneal sarcomas (RPSs) are rare cancers with some variability in clinical and histopathological presentation. In Germany, general treatment strategies of retroperitoneal sarcoma are unknown since centralized registries do not exist. The objective of this survey was to access the medical care of RPS patients in Germany. Methods: In cooperation with the German Society of General and Visceral surgery, the German Interdisciplinary Sarcoma Study Group and the patient advocacy group Das Lebenshaus we designed an online survey assessing diagnostic and treatment strategies (e. g. performance of tumor biopsies, administration of multimodal therapies and surgical strategy). All departments for general and visceral surgery in Germany were addressed (n = 976). Results: Responses were received from 191 of 976 departments. Only 11 surgical departments treat more than 10 RPS patients per year. A multidisciplinary sarcoma board exists in 19 hospitals. Staging is generally performed by cross-sectional imaging. In 54% of the departments pretreatment tumor biopsy is a standard procedure. Surgery is performed as compartment resection in 85% of the departments. A systematic lymph node dissection is done in 40%. Adjuvant radio- or chemotherapy is performed as a standard treatment in 27% and 22% departments, respectively. Conclusion: The survey demonstrates a large heterogeneity in RPS diagnostic and treatment strategies. Dedicated education programs and centralized treatment strategies are warranted to improve the standard of care.